APLIKASI SISTEM INFORMASI KOPERASI SIMPAN PINJAM UNTUK KEANGGOTAAN PADA KOPERASI PEDAGANG PASAR CIRACAS (KOPPAS CIRACAS) DENGAN MENGGUNAKAN METODE EXTREME PROGRAMING BERBASIS ANDROID - Rejeki, Sri (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2019)
Cooperatives are non-bank institution legal entities aimed at the welfare of its members, in the form of financial business that is currently developing in DKI Jakarta very often used as daily savings and loans for members, with regulations in the field of cooperatives in Law No. 25 of 1992 concerning cooperatives. With Android-based technology and websites commonly used in the development of financial technology, FINTECH is wanted to be able to help cooperative systems that make it easier and save time. Cooperative applications created using Android Studio as interfaces with extreme programming system methodology used by members can see the cooperative application menu displayed online as an effort to minimize the possibility of members coming directly to the cooperative. Display in the application to find out balances, incoming transactions, accounts receivable money transactions, withdrawal and recapitulation transactions. At the end of this thesis will be made a cooperative information system using a PHP program, MySQL Database and KOPPAS android-based savings and loan cooperative application.Â Keywords: Information Systems, Services, Cooperatives, Android